Analysis of the effectiveness of aromatherapy with essential oil of Ylang ylang in anxiety disorders: a literature review (Research, Society and Development, 2021)
Anxiety is a health problem that affects people of all ages and social classes. It is characterized as a natural mechanism that leads human beings to fear and flee from real danger situations, but it is often associated with the individual's psychological states, directly impacting their quality of life. The use of natural therapies for the treatment of this disorder is increasingly high, especially due to its low cost, effectiveness and focus on the patient as a whole. Among them, aromatherapy, a holistic method that uses volatile compounds of plant origin that act in the body improving physical and mental well-being through inhalation, topical use or ingestion. A literature review was carried out on anxiety and aromatherapy with ylang ylang essential oil, with the aim of analyzing scientific data on the effectiveness of this natural therapy in the presence of anxiety disorders. The data demonstrate that the synergy of the phytoconstituents present in this essential oil performs favorable actions for the treatment of anxiety.